Why does CRT work better in women?. (3rd October 2022) - Lorente Ros, A; Monteagudo, J M; Calvi, V; Sancho-Tello, M J; Maass, A H; Van Erven, L; Ellery, S; Nurnberg, M; Voros, G; Vernooy, K; Quesada, A; Martinez, J G; et al.
Abstract: Introduction: It has been recently postulated that cardiac resynchronization therapy (CRT) might have a higher efficacy in women, with a greater reverse cardiac remodeling in this population. The reasons for these differences are not yet completely understood. We aimed to detect sex differences in the degree of ventricular asynchrony (VA) and mitral regurgitation (MR) in patients undergoing CRT implantation. Methods: We analyzed baseline characteristics of a prospective international clinical trial that compared CRT response rate in a HF population with a comparable distribution of men and women (BIOWOMEN). A total of 408 patients were analyzed. The degree of mitral regurgitation and intra and inter-ventricular asynchrony was assessed by independent echocardiographers in a core lab. Inter-ventricular asynchrony was defined as an interventricular mechanical delay greater than 40ms and intra-ventricular asynchrony as differences greater than 50ms among regional pre-ejection periods. Multivariable logistic regression was performed using commercial data analysis software. Results: As expected, ventricular asynchrony was dependent on QRS duration and the presence of LBBB (p<0.01). Baseline QRS duration was significantly shorter in women than men (155.85±19.0 in women vs 160.4±21.6, p=0.02). However, for a similar QRS duration, there were no differences in asynchrony parameters between the two groups (p=0.43; Figure 1). Female sex was associated with a significantly higher proportion of mitral regurgitation for a given QRS duration, which was independent of the etiology (p=0.05). Conclusions: In our analysis, for a given QRS duration there was not a higher degree of asynchrony in women with HF. However, female sex was associated with a significantly higher proportion of mitral regurgitation for a given QRS duration irrespective of baseline HF etiology. Further investigations are needed to establish a possible link between these findings and better CRT outcomes in women. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): BIOTRONIK SE & Co. KG